Characterizing pearlite transformation in an API X60 pipeline steel through phase-field modeling and experimental validation - Araghi, Mohammad Y.; Parsa, M. H.; Ghane Ezabadi, Mostafa; Roumina, Reza; Mirzadeh, Hamed; Xu, Shuozhi (Frontiers in Materials, 2024)
This study explores the microstructural characterization of pearlite phase transformation in high-strength low-alloy API X60 steel, which is used in pipelines. Understanding the formation, phase percentages, and morphology of the pearlitic phase is crucial since it affects the mechanical properties of the considered steel. In this research, a phase-field model, particularly the Cahn–Hilliard approach, was used in order to simulate the formation and morphology of the pearlite phase in response to different heat treatments. Both double- and triple-well potentials were considered for comprehensively studying pearlite’s morphology in the simulations. The simulation results were then compared with experimental outcomes obtained by metallography and field-emission scanning electron microscopy analyses. Considering the double-well potential can help simulate only two phases, ferrite and cementite, which is less compatible with the experiment results than the triple-well potential, which gives the possibility of simulating a three-phase microstructure, ferrite, cementite, and austenite, and a better match with experimental data. The study revealed that as the cooling rate increases, the interlamellar spacing and layer thickness decrease. Additionally, the difference between experimental and simulation results using triple-well potential was approximately ∼10%. Therefore, triple-well potential formulation predictions have better agreements with experimental results for the development circumstance of pearlitic structures.